Cash transfers and inflation: An overview of the evidence - Allen IV, James; Gentilini, Ugo (International Food Policy Research Institute, 2025)
Cash transfer programs are a leading form of social assistance, reaching up to 21 percent of the population in at least 68 low- and middle-income countries (World Bank 2025). Between 1980 and 2023, a total of 1.4 million papers were produced on the matter (Gentilini 2024) and more have been published since. While the design and impact of these and related programs have been closely studied (Banerjee et al. 2024), much less is known about whether or not cash transfer programs cause increases in the market price of good and services—that is, inflation. By reducing the purchasing power of money, program-driven inflation can diminish the positive impacts of cash transfers for recipients and create a negative spillover for nonrecipients, thus undermining program aims of improving social welfare. Recent literature on cash transfers and inflation is limited and often described as dichotomous: on one side, Egger et al. (2022) and other studies find little to no effect, while, on the other side, Filmer et al. (2023) find sizable and alarming inflationary effects on selected commodities. However, a closer look at these and other papers reveals that their results are less contradictory than they first appear. Rather, the whole body of the current literature is congruous with the hypothesis that cash transfers have minimal average effects on prices for most market goods; but these transfers can cause inflation where they significantly increase market demand for goods for which supply is relatively inelastic. This review proceeds as follows. We first present a simple conceptual model that illustrates the theoretical basis for this hypothesis, followed by an overview of the studies included in the review and their key differences. The next section presents a synthesis of the main findings in the existing empirical evidence. We then look at related research just outside the purview of this review. The conclusion discusses key takeaways.